A Built-In Controller and Extended BS Architecture for Prototype Debug and Test - Gustavo R.Alves (1999)
Prototype validation is becoming a major concern and hardship in modern electronic products design and development. Simulation, structural test, functional debug and timing debug are all constituting parts of the validation process, although very often they are addressed as independent and dissociated tasks. In this paper we describe an integrated approach to board-level prototype validation, based on a set of mandatory / optional BST instructions and a built-in controller for debug and test, that addresses the late mentioned tasks as inherent parts of a whole process.